Directed threat imagery in generalized anxiety disorder. Issue 4 (24th July 2017) - Buff, C.; Schmidt, C.; Brinkmann, L.; Gathmann, B.; Tupak, S.; Straube, T.
Abstract : Background: Worrying has been suggested to prevent emotional and elaborative processing of fears. In cognitive-behavioral therapy (CBT), generalized anxiety disorder (GAD) patients are exposed to their fears during the method of directed threat imagery by inducing emotional reactivity. However, studies investigating neural correlates of directed threat imagery and emotional reactivity in GAD patients are lacking. The present functional magnetic resonance imaging (fMRI) study aimed at delineating neural correlates of directed threat imagery in GAD patients. Method: Nineteen GAD patients and 19 healthy controls (HC) were exposed to narrative scripts of either disorder-related or neutral content and were encouraged to imagine it as vividly as possible. Results: Rating results showed that GAD patients experienced disorder-related scripts as more anxiety inducing and arousing than HC. These results were also reflected in fMRI data: Disorder-related v. neutral scripts elicited elevated activity in the amygdala, dorsomedial prefrontal cortex, ventrolateral prefrontal cortex and the thalamus as well as reduced activity in the ventromedial prefrontal cortex/subgenual anterior cingulate cortex in GAD patients relative to HC. Conclusion: The present study presents the first behavioral and neural evidence for emotional reactivity during directed threat imagery in GAD. The brain activity pattern suggests an involvement of a fear processing network as a neural correlate of initial exposure during directed imagery in CBT in GAD.